Reaktualisasi Hukum Waris Islam Di Indonesia - Abd. Muni (Al Hikmah: Jurnal Studi Keislaman, 2019)
Abstract. In Indonesia, the problem of inheritance is a problem that is immediately confused with the concept of muamalah and social activities that require a lot of attention along with the times. This relates to the existence and preservation of Islamic law in Indonesia, especially in the area of inheritance law. The existence of three positive legal concepts that are equally accepted as sources of law in Indonesia, namely European law, customary law and Islamic law, do not make Islamic legal values more or less eroded by two other laws, at least able to become the main law for the people Islam and for those who follow the principle of Islamic personality. In this journal, we will discuss several definitions of inheritance from the three sources of law, then what is the nature of inheritance law itself, which the writer can summarize into several parts, including two main concepts that greatly affect the distribution of inheritance, namely the existence of patrilineal and bilateral concepts. Therefore, it is important to review the distribution of this inheritance from a variety of perspectives and certainly against the background of the thoughts of figures such as Munawwir Syadzali and Hazairin and the concept of inheritance of the Arab nation. The difference in concept includes how receptie theory which is seen as contradictory to the Constitution and Pancasila and even the Qur'an and As-Sunnah will be discussed through several approaches including historical approaches, fiqh and maslahah mursalah. It is intended that Islamic law will continue to be accepted, applied and even become a basic reference for law enforcement agencies such as the Religious Courts as stipulated in legal considerations so as to produce a rule of law which is based on the principles of benefit and justice. The actualization of inheritance law in Indonesia is indeed very much needed for the existence of Islamic inheritance law itself. Keywords: Inheritance law, legal system, bilateral principles, patrilineal, decision of the Religious Court, receptie theory